Corrosion inspection and monitoring - Roberge, Pierre R. (Wiley series in corrosion., 2007)
The comprehensive reference on modern techniques and methods for monitoring and inspecting corrosion. Strategic corrosion inspection and monitoring can improve asset management and life cycle assessment and optimize operational budgets. Advances in computer technologies and electronics have led to very efficient tools for monitoring and inspecting corrosion, including impedance spectroscopy, electrical field signatures, acoustic emissions, and radiographs.